Investigating Transgressive Segregation to Improve Yield in \(F_2\) Segregants of Sesame (Sesamum indicum L.): A Comprehensive Study - Ravi, Greeshma; B., Lovely; G., Seeja; Thara, Susha S; C., Ninitha Nath; K.B., Amritha (Current Research Progress in Agricultural Sciences Vol. 10, 2025)
Sesamum (Sesamum indicum L.), one of the most ancient oil crops, has been referred to as the ‘queen of oilseeds’ by virtue of its high-quality oil. The experiment involved the F2 generation of three superior crosses of sesame: Thilak X Ayali 1, Thilathara X Ayali 2 and Thilak X Ayali 5, grown in a Compact Family Block Design. A total of 200 plants were grown with a spacing of 30 x 25 cm, and observations were recorded on yield-related characters. Biometric observations were recorded for nine characters viz, days to first flowering, number of primary branches, number of capsules per plant, capsule length (cm), capsule width (cm), number of seeds per capsule, days to maturity, plant height (cm) and seed yield per plant (g). The data were subjected to analysis of variance (ANOVA) and various genetic parameters were worked out using GRAPES software, version 1.1.0. Significant variation was found among most traits, except for capsule length, capsule width, number of seeds per capsule and the number of primary branches. Maximum coefficient of variation was recorded for number of capsules per plant (41.091) followed by seed yield per plant (40.163). The least coefficient of variation was recorded for capsule length (6.58) closely followed by the number of seeds per capsule (6.774). The cross Thilathara X Ayali 2 exhibited a high frequency of transgressive segregants for multiple traits, particularly for seed yield per plant, making it highly promising for further breeding efforts. Plant height had the highest mean and range, showing considerable potential for selection. CV analysis revealed high variability for traits like the number of capsules per plant and seed yield per plant. In contrast, low variability and high stability were observed for traits like capsule length, number of seeds per capsule and days to maturity. Higher PCV and GCV were recorded for traits like days to first flowering, number of capsules per plant, and seed yield per plant, showing substantial genetic and environmental influences. Moderate PCV and GCV were found for plant height and days to maturity, while traits like capsule length, number of seeds per capsule, and capsule width had the lowest PCV and GCV, indicating limited genetic variation. Days to first flowering and days to maturity showed high heritability combined with high genetic advance, suggesting the preponderance of additive gene action and are ideal for simple selection. Traits like capsule length, capsule width, and number of seeds per capsule showed low heritability and genetic advance, making them less ideal for selection. The cross, Thilathara X Ayali 2 should be prioritized in future generations to recover desirable segregants, especially for economically important traits like seed yield. In conclusion, it has been found that while certain traits are more influenced by genetic factors and suitable for selection, others are heavily impacted by environmental variability.